A novel PDPN antagonist peptide CY12-RP2 inhibits melanoma growth via Wnt/β-catenin and modulates the immune cells - Chunyan Feng; Albert Yu; Zhongfu Wang; Kun Wang; Jiawei Chen; Yaojiong Wu; Ting Deng; Huaqing Chen; Yibo Hou; Shaohua Ma; Xiaoyong Dai; Laiqiang Huang (Journal of Experimental & Clinical Cancer Research, 2024)
Abstract Background Podoplanin (PDPN) is a highly conserved, mucin-type protein specific to the lymphatic system. Overexpression of PDPN is associated with the progression of various solid tumors, and plays an important roles in the tumor microenvironment by regulating the immune system. However, the role of PDPN-mediated signal activation in the progression of melanoma is still unknown. Methods PDPN expression was first analyzed in 112 human melanoma tissue microarrays and melanoma cell lines. Functional experiments including proliferation, clone formation, migration, and metastasis were utilized to identify the suppressive effects of PDPN. The Ph.D.TM-12 Phage Display Peptide Library was used to obtain a PDPN antagonist peptide, named CY12-RP2. The immunofluorescence, SPR assay, and flow cytometry were used to identify the binding specificity of CY12-RP2 with PDPN in melanoma cells. Functional and mechanistic assays in vivo and in vitro were performed for discriminating the antitumor and immune activation effects of CY12-RP2. Results PDPN was overexpressed in melanoma tissue and cells, and inhibited melanoma cells proliferation, migration, and metastasis by blocking the EMT and Wnt/β-catenin pathway. PDPN antagonistic peptide, CY12-RP2, could specifically bind with PDPN, suppressing melanoma various functions inducing apoptosis in both melanoma cells and 3D spheroids. CY12-RP2 also enhanced the anti-tumor capacity of PBMC, and inhibited melanoma cells growth both in xenografts and allogeneic mice model. Moreover, CY12-RP2 could inhibit melanoma lung metastasis, and abrogated the immunosuppressive effects of PDPN by increasing the proportion of CD3 + CD4 + T cells, CD3 + CD8 + T cells, CD49b + Granzyme B + NK cells, and CD11b + CD86 + M1-like macrophages and the levels of IL-1β, TNF-α, and IFN-γ. Conclusions This study has demonstrated the important role of PDPN in the progression of melanoma and formation of immunosuppressive environment, and provided a potential approach of treating melanoma using the novel CY12-RP2 peptide. Graphical Abstract In melanoma, PDPN is overexpressed in the cancer cells, and promotes melanoma cells growth and metastasis through activating the Wnt/β-catenin pathway. Treatment with the PDPN antagonistic peptide CY12-RP2 could not only inhibit the melanoma growth and metastasis both in vitro and in vivo through Wnt/β-catenin pathway blockade, but also abrogate the immunosuppressive effects of PDPN through modulating immune cells.